Migration and Foreign Remittances in the Philippines - Burgess, Robert; Haksar, V. (Washington, D.C. : International Monetary Fund, 2005)
International migration and large remittance flows have been prominent features of the Philippine economy for many decades. This paper describes the evolving pattern of migration and remittance flows and analyzes some of the channels through which remittances affect economic activity. The empirical evidence does not clearly support the purported short-term stabilizing effect on consumption of remittance flows. Furthermore, as in other countries, the longer term economic effect of such flows is ambiguous.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet